Geopolitics : re-visioning world politics - Agnew, John A. (Routledge, 2003)
Geopolitics identifies and scrutinizes the central features of geopolitics from the sixteenth century to the present, paying close attention to its persisting conceptual underpinnings, novel turns and shifting impacts.